Oral bacillus Calmette-Guérin vaccine against tuberculosis: why not? - Monteiro-Maia, Renata (Mem Inst Oswaldo Cruz, 2014)
The bacillus Calmette-Guérin (BCG) vaccine is the only licensed vaccine for human use against tuberculosis (TB). Although controversy exists about its efficacy, the BCG vaccine is able to protect newborns and children against disseminated forms of TB, but fails to protect adults against active forms of TB. In the last few years, interest in the mucosal delivery route for the vaccine has been increasing owing to its increased capacity to induce protective immune responses both in the mucosal and the systemic immune compartments. Here, we show the importance of this route of vaccination in newly developed vaccines, especially for vaccines against TB.